Posesión efectiva, titularidad del procedimiento y sus efectos jurídicos - Nieto Campaña, Ángel Belisario (2025)
This research focuses on the problem of legal uncertainty surrounding effective possession in Ecuador and the legal implications of notarial actions, identifying possible violations of the rights of beneficiaries. The lack of clear and up-to-date regulations and procedures allows a single heir to carry out the procedure, violating the rights of the other co-heirs to participate in the inheritance. The objective is to analyze the procedure of effective possession in violation of the right to a fair and equitable succession, as well as the legal effects of the Ecuadorian notary. A qualitative methodology was used, with an analytical, descriptive, and documentary approach, conducting a study of legal content, doctrines, and jurisprudence, in addition to interviews with lawyers and heirs. The findings indicate that it is essential to increase legal certainty in notarial and judicial procedures to prevent the violation of property and procedural rights. Lack of clarity in the rules and poor management can lead to delays, unnecessary expenses, and disputes among heirs, undermining equity in access to inheritance. More fluid collaboration between notaries and judges is highlighted, especially in complex situations involving property disputes, to ensure transparency and protect the rights of all participants, including third parties. In conclusion, the process of effective possession in Ecuador requires evaluation to guarantee notarial and judicial intervention and promote fair inheritance, preventing violations of the rights of heirs and ensuring legal certainty in the transfer of assets.